2021
DOI: 10.1021/acs.accounts.1c00298
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ligand Carboxylates on Electrocatalyzed Water Oxidation

Abstract: orientation of two ruthenium centers encapsulating the carboxylate containing noninnocent ligand f ramework in electro-and photochemical WO was reported. Two wellcharacterized ruthenium complexes (cis and trans) with very similar ligand scaf folds were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…[ 9 ] It has been confirmed that the carboxylate group in the ruthenium complexes can improve water oxidation in three ways: 1) accelerating the CPET process; 2) stabilizing the high oxidation states of the metal center; 3) improving the stability of catalysts by the strong coordination with metal centers. [ 6b,10 ] Similar results were also observed for metal‐organic frameworks. [ 6b,9a ] These findings inspire us to upgrade the design of NiFe LDH through a biomimetic process to accelerate the sluggish kinetics.…”
Section: Introductionsupporting
confidence: 70%
“…[ 9 ] It has been confirmed that the carboxylate group in the ruthenium complexes can improve water oxidation in three ways: 1) accelerating the CPET process; 2) stabilizing the high oxidation states of the metal center; 3) improving the stability of catalysts by the strong coordination with metal centers. [ 6b,10 ] Similar results were also observed for metal‐organic frameworks. [ 6b,9a ] These findings inspire us to upgrade the design of NiFe LDH through a biomimetic process to accelerate the sluggish kinetics.…”
Section: Introductionsupporting
confidence: 70%
“…As shown in Scheme 2, the calculated p K a of 3 2 is around 11, while the calculated H 2 O→OH − ligand exchange has an exothermicity of 7.2 kcal mol −1 , indicating both pathways are feasible, but the latter pathway could be more favorable at the experimental pH of 11.5. In the third pathway (III), the formation of .+ L−Cu II −OH − may transpire via the proton‐coupled electron transfer, a prevalent process in electrochemical reactions [91–98] . However, such a process is associated with a redox potential of 1.39 V and thus less unfavorable compared to the pathway 3 2 → 3 3′ .…”
Section: Resultsmentioning
confidence: 99%
“…In the third pathway (III), the formation of * + LÀ Cu II À OH À may transpire via the proton-coupled electron transfer, a prevalent process in electrochemical reactions. [91][92][93][94][95][96][97][98] However, such a process is associated with a redox potential of 1.39 V and thus less unfavorable compared to the pathway 3 2! 3 3'.…”
Section: Formation Of Active Speciesmentioning
confidence: 99%
“…[13] The abovementioned negatively charged groups also contribute to lower the overpotentials once directly coordinated to the catalytic sites. [14] However, it is challenging to simultaneously incorporate these groups in the inner and outer coordination environments, and complete protonation of more basic groups such as pyridines and more basic oxygenated bases also prevents their wide applications under acidic conditions. [15] Alternatively, the ubiquitous hydrophobic interactions have been shown to significantly influence activities in enzymatic catalysis and molecular devices through stabilizing the intermediates.…”
Section: Introductionmentioning
confidence: 99%